2020
DOI: 10.1093/jxb/eraa520
|View full text |Cite
|
Sign up to set email alerts
|

Variation between rice accessions in photosynthetic induction in flag leaves and underlying mechanisms

Abstract: Several breeding initiatives have sought to improve flag leaf performance as its health and physiology are closely correlated to rice yield. Previous studies have described natural variation of photosynthesis for flag leaves; however, none have examined their performance under the non-steady-state conditions that prevail in crop fields. Photosynthetic induction is the transient response of photosynthesis to a change from low to high light. Rice flag leaf photosynthesis was measured in both steady- and non-stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 50 publications
6
34
2
Order By: Relevance
“…In rice, it might not be as clearly defined (De Souza et al, 2020 ; Soleh et al, 2016 ). Previously, it was shown that photosynthetic induction in rice is heavily limited by stomata (Yamori et al, 2020 ) as well as biochemistry (Acevedo‐Siaca, Coe, Quick, et al, 2020 ; Acevedo‐Siaca, Coe, Wang, et al, 2020 ). Indeed, previous work has shown that QTLs that increase stomatal conductance in rice can increase the initial slope of CO 2 assimilation during induction (Adachi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In rice, it might not be as clearly defined (De Souza et al, 2020 ; Soleh et al, 2016 ). Previously, it was shown that photosynthetic induction in rice is heavily limited by stomata (Yamori et al, 2020 ) as well as biochemistry (Acevedo‐Siaca, Coe, Quick, et al, 2020 ; Acevedo‐Siaca, Coe, Wang, et al, 2020 ). Indeed, previous work has shown that QTLs that increase stomatal conductance in rice can increase the initial slope of CO 2 assimilation during induction (Adachi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence that stomatal opening and closing can vary by rice subpopulation (Qu et al, 2016 ), with japonica accessions having an overall slower stomatal response. Additionally, none of the accessions utilized in these independent photosynthetic induction studies have overlapped (Acevedo‐Siaca et al, 2020b ; Acevedo‐Siaca, Coe, Wang, et al, 2020 ; Adachi et al, 2019 ; Yamori et al, 2020 ). Furthermore, the release date for the accessions utilized in different induction studies in rice vary greatly (Acevedo‐Siaca et al, 2020a , 2020b ; Yamori et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations